Effects of sugarcane bagasse ash and nano eggshell powder on high-strength concrete properties. (December 2022) - Amin, Mohamed; Attia, Mohammed M.; Agwa, Ibrahim Saad; Elsakhawy, Yara; el-hassan, Khaled Abu; Abdelsalam, Bassam Abdelsalam
Abstract: There are many problems due to the cement industry around the world besides the air pollution by greenhouse gas emissions. The problem arises when a dense quantity of CO2 is emitted through the conversion of calcium carbonate lime (CaCO3 ) into calcium oxide lime (CaO), the main ingredient in cement. This transformation is made in an oven-dry by burning fossil fuels, in a process that releases more carbon dioxide. In this study, sugarcane bagasse ash (SCBA) and nano eggshell powder (NEP) are considered cementitious materials and were added to the cement at different percentages to reduce the cement contents in the concrete industry. Sixteen high-strength concrete (HSC) mixtures experimented with in this investigation contain SCBA and NEP other than the control mix. The SCBA and NEP were added to cement content by 5 %, 10 %, 15 %, and 20 % for SCBA, and 2.5 %, 5 %, and 7.5 % for NEP. This study evaluates the fresh and hardened properties of HSC. Also, EDX and SEM analyses were conducted on the SCBA, NEP, and HSC concrete to analyze the microstructure. The experimental results exhibited that the setting time of HSC is delayed by increasing the SCBA ratio by 25 % of the control mix. Adding NEP accelerates the HSC setting time compared with the control mix. The best mixture result includes 5 % NEP with 15 % SCBA, which exhibited a dense form, no pores, and no cracks, as analyzed in the microstructure.